Upaya Bhabinkamtibmas Dalam Mencegah Peredaran Minuman Keras Ilegal Melalui Penyuluhan Di Wilayah Hukum Polresta Cirebon - Ekananta, Danny Feizal (Indonesian Journal of Police Studies, 2020)
This research is motivated by problems caused by the consumption of illegally circulating liquor. Preemptive and preventive efforts are made to prevent the circulation of illegal alcohol. Therefore, a study was conducted which aimed to find out the progress of the implementation of these efforts through the efforts of Bhabinkamtibmas through counseling, as well as the influencing factors. This research was conducted with a qualitative approach, which is a type of descriptive research, as well as data collection techniques with interviews, observations, and document review. Then analyzed with data reduction techniques, data presentation, and drawing conclusions / verification. The results of the study found that the counseling efforts carried out by Bhabinkamtibmas were not yet maximal in terms of planning, implementation, and supervision and control. Analysis of the implementation of counseling does not affect the change in mindset of the community to obey the law. In addition, the lack of insight into the knowledge of members of Bhabinkamtibmas makes counseling of citizens only run as it is without meeting planned targets or goals. While the inhibiting factors are organizational factors, human resource factors, facilities and infrastructure factors, as well as the cultural factors of the people of Cirebon Regency and communication factors. Based on the results of the study, the authors suggest that even distribution of personnel in each police station is in accordance with the duties and functions of the members entailed. Providing online training through the zoom application to Binmas personnel, equipping officers with the ability to master technology and the science of social communication. Counseling efforts are targeted at young people, regional communities, places of education, and places of entertainment. Require Bhabinkamtibmas to guide Perkap Number 22 Year 2007 and Perkap Number 3 Year 2015, hone creativity and innovation in conducting counseling, and improve the quality of Bhabinkamtibmas, Kasas Binmas can develop Bhabinkamtibmas well in a planned and structured manner.